The Effectiveness of Adolescent Reproductive Health Education on Attitude in Facing Pre Menstrual Syndrome in Students of Class X OTKP At SMKN 1 Binjai in 2018 - Lusiana Gultom (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
One of the children's health efforts at community health center, established through the Presidential Instruction, is the Youth Care Health Service (PKPR), specifically aimed at increasing the knowledge and skills of adolescents about the reproductive health. Based on the Indonesian Health Profile, it was known that 11 provinces (32.4%) have not achieved the Strategic Plan target, set at 30%, in 2016, North Sumatra province reached 23.47%. Common problems in adolescents related to menstruation are dysmenorrhea (67.2%) and pre-menstrual syndrome (PMS) 63.1%. Pre-menstrual syndrome (PMS) is a collection of physical, emotional, psychological symptoms experienced by women during the luteal phase of each menstrual cycle (7-14 days before menstruation). This study aims to determine the Effectiveness of Adolescent Reproductive Health Education Against Attitudes in Facing Pre Menstrual Syndrome in Students of Class X OKTP at SMKN 1 Binjai 2018. This study used one group Pretest Postest design. All students of grade 10 OTKP, 83 people, became the population in this study, and the entire population was used as a research sample. The primary data, collected through questionnaire sheets, were analyzed by the Wicolxon Test. Through the research with the wicolxon test, it was found that the p value was 0,000, where the p value was 0,000 <α (0,05), then H0 was rejected which means that this research was meaningful, and this study concluded that adolescent reproductive health education was effective in increasing the attitude of female students in facing the pre menstrual syndrome. The results of the study are expected to be information and literature material for further research, health workers are also expected to provide child health counseling.